Seed Germination Response of Rauvolfia serpentina Benth. to Certain Physical and Chemical Treatments - Paul, D; Paul, NK; Basu, PK (Journal of Bio-Science, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI:10.3329/jbs.v16i0.3756 J. bio-sci. 16: 129-131, 2008